Pengaruh Variasi Temperatur Torefaksi Terhadap Karakteristik dan Nilai Kalor dari Produk Briket Arang Eceng Gondok - Muhammad Zainul Aris; Yasir Amani (Machine : Jurnal Teknik Mesin, 2023)
Energy is needed by all people in various countries, this results in climate change and depletion of energy, it is necessary to find clean alternative energy, one of which is biomass. Water hyacinth is a biomass that grows rapidly in Indonesia, but its energy density is still low. This research aims to improve the characteristics and calorific value of water hyacinth biomass using torefaction process. In this study, water hyacinth was subjected to a torefaction process with temperature variations of 200 ℃, 250 ℃ and 300 ℃ and a holding time of 1 hour. ¬The biochar resulting from the torefaction process is then made into briquettes using tapioca starch adhesive, with a ratio of 10% of the weight of the raw material, and pressing at a pressure of 300 kg/cm2. From the research and testing that has been done, the proximate test results obtained the lowest moisture content of 5.75% in the 300 ℃ sample, the lowest ash content of 17.65% in the 200 ℃ sample, the lowest volatile compounds of 39.52% in the 300 ℃ sample and the highest fixed carbon of 25.92% in the 300 ℃ sample. The highest heating value was produced in the 300 ℃ sample which amounted to 5140.44 cal/g. The lowest Shatter Index was 1.68% in the 300 ℃ sample. The most optimal burning rate of briquettes in the 300 ℃ sample was 0.085 g/min with a duration of 47 minutes. The results of this study indicate that the torefaction process and torefaction temperature variation have a significant effect on the characteristics and heating value of water hyacinth briquettes. Key words : Torefaction, Water Hyacinth, Characteristics, Calorific Value, Briquettes.